Application of percutaneous biliary drainage in the treatment of post-operative bile leakage after liver rupture: A case report - Jinlong Chen; Zhikuan Wang; Lixin Zhang; Xi Chen; Yuanyuan Liu; Hong Chen; Xiaoqiang Tong; Yanchao Dong (Journal of Minimal Access Surgery)
Post-operative bile leakage (POBL) is a serious complication following hepatobiliary surgery, with potentially life-threatening consequences if left untreated. This article presents a successful case of POBL management without surgical intervention. A 31-year-old male, diagnosed with bile leakage before hospitalisation, underwent percutaneous biliary drainage (PTBD) to address bilomas. Follow-up after 3 months indicated biloma atrophy and POBL healing but revealed bile duct stenosis. The patient received a larger biliary drainage tube, and after 1 month, the biloma and tube were removed. A 1-year follow-up confirmed the patient’s excellent health. This case underscores the safety and efficacy of PTBD for managing POBL, offering a non-invasive alternative for patients with this complication. PTBD presents a viable treatment option for POBL cases, minimising the need for surgical interventions and their associated risks.